Investment Coordination and Demand Complementarities - Jean-Marie Baland; Patrick Fracois (Queen's University, Department of Economics, 1996)
This paper analyzes the possibility of investment coordination leading to outcomes which dominate non-investment equilibria in the presence of monopolistic competition. We establish when complementarity leads to investment coordination failures and explore the welfare implications of coordinated investment. Our main results caution against demand complementarities as a motive for investment coordination. We find that: 1) generally, a strict notion of complementarity (Hicks) is necessary for the existence of an investment coordination problem and 2) that when the problem does exist, coordination often lowers social welfare.
Keywords: O14; O33; L13; L16; 330